Un mix di tecnologie per accrescere la fruizione e l’accessibilità alla rete delle 100 chiese romaniche della Sardegna - Figus, Antonello (Archeomatica, 2024)
The knowledge, promotion and valorisation of Italy's Cultural Heritage express an extraordinary value in the international cultural panorama. Italy contains the major sites of cultural, archaeological and landscape interest which should be accessible to all. The “Sardinia Isola del Romanico” Foundation was created with the aim of showing the great monumental heritage of the Sardinian Middle Ages, represented by over 150 Romanesque monuments located throughout the island. To increase the use of these monuments it is essential to promote their real and virtual accessibility, introducing in both cases the use of new information and digital technologies. Accessibility has therefore become the key word to achieve this objective, which allows everyone to enjoy cultural heritage, breaking down distances and barriers.